Baseline susceptibility of cotton leafhopper, Amrasca biguttula biguttula against different insecticides in Punjab - Sandhu, Rajwinder Kaur; Kang, B K (Indian Journal of Plant Protection, 2020)
Studies were carried out to determine the baseline susceptibility of cotton leafhopper, Amrasca biguttula biguttula (Ishida) to novel insecticides viz., dinotefuran, tolfenpyrad, flonicamid and thiamethoxam for the populations collected from different cotton growing areas viz., Ludhiana, Muktsar, Mansa and Abohar of Punjab. New molecule, dinotefuran with LC50 values ranging from 0.00007 per cent (Ludhiana) to 0.00013 per cent (Abohar) proved to be extremely toxic against all the tested populations followed by tolfenpyrad and flonicamid while thiamethoxam was found to be the least toxic with LC50 values ranging from 0.00082 to 0.00218 per cent. Baseline data of these new chemistry molecules will be very helpful to detect the resistance levels developed by this pest in future.